(untitled) (Research, Society and Development, 2024)
Prescribing plays a decisive role in promoting the rational use of medications and is the main cause of medication errors. Given the possibility of preventing such failures, this study aims to verify compliance with current legislation, evaluate the WHO prescribing indicators, identify the nature of prescription errors, and propose strategies to minimize them. To this end, a quantitative descriptive cross-sectional study was carried out, through data collection of prescriptions seen at a Basic Health Unit in Araçatuba-SP. The results showed that of 350 prescriptions, only 8 (2.3%) showed no irregularity, on the other hand, the prescriptions were aligned with the profile recommended by the WHO indicators. Thus, it is possible to conclude that the good performance of the prescription indicators demonstrates an efficient work of the professionals involved in health care. On the other hand, the failures committed by noncompliance with the current rules are of 2 human nature and of the work system (manual prescription). Thus, the training of prescribers and pharmacists, the implementation of electronic prescriptions, and the increase of surveillance are strategies that can be adopted to reduce the errors identified in this study.